Significance of D-dimer in Assessment of Severity and Mortality of COVID-19 Patients A Tertiary Care Hospital Study - Ashwini Suruthy; Neethu Gowdru Vishwanathan; Seema Bijjaragi (Medical Laboratory Technology Journal, 2022)
The outbreak of COVID-19 has brought public health emergency worldwide and has been the biggest challenge to date. This study aims to study the correlation between D-dimer levels with severity and mortality in COVID-19 patients. This study will help us understand the disease's progression and monitor the disease severity and mortality in Covid-19 patients. This retrospective descriptive study was conducted over four months from April 2021- to June 2021 in a tertiary care hospital in Central Karnataka. Demographic details and clinical and laboratory parameters were obtained from electronic hospital records. Inclusion criteria are Patients who were RT-PCR confirmed positive cases were only included in this study. Exclusion criteria are Patients who had cancer, hematologic malignancies, and acute coronary syndrome were all excluded. Results of the research are A total of 75 cases were evaluated and analyzed in this study. Patients were categorized based on severity as mild to moderate and severe. Out of which 50 patients had recovered from the illness, and 25 patients have succumbed to death. Our study revealed that elevated D-dimer levels were significant (p<0.02) with the outcome of the disease, and with the mean level of 929.27 in severe patients and 466.47 in mild-moderate patients, elevated D-dimer were highly significant (p<0.001) with the severity of the disease. Conclusion research detailed investigations of 75 COVID-19 patients suggests that a significant increase in D-dimer levels was associated with mortality and severity of the disease. Therefore, we strongly recommend that the D-dimer be used to screen patients with COVID-19 to evaluate the severity and predict the prognosis and mortality in hospitalized COVID-19 patients during admission and follow-up throughout hospitalization.